Thesis workshops in Social and Human Sciences Doctorates, a study in Argentinian universities - Cruz, Tamara (2022)
Doctoral thesis constitutes a milestone in research training. Based on the low graduation rates and the high time to degree in doctoral programs in Social and Human Sciences, the aim of this study was to investigate the training activities of the thesis workshop as a pedagogical strategy for research training in doctoral programs in Buenos Aires Autonomous City. A qualitative, descriptive, and exploratory study was carried out, data analysis finished in 2019. The sample is conformed by six doctoral programs and sixteen interviews. Data collection methods were semi-structured interviews to heads of the doctoral programs, thesis workshop professors, and documentary analysis. Thesis workshop learning outcomes, location in the curricula, contents and teaching strategies were inquired. Three doctoral programs offered long term support in the making of the thesis, from the definition of the research problem to the writing of specific sections of the doctoral thesis, offered from the beginning of the course and extending throughout the course of the doctorate. From the results, it was concluded that when some characteristics of the communities of practice occur and remain in time, it is possible that thesis workshops in this field can become pedagogical devices for research training. Future research can delve into these conclusions by offering more detail including other areas to this analysis, such as observing thesis workshop meetings o linking completion rates with the workshops offered.